Predictive Factors Associated with Survival in Female Gastric Cancer Patients in Southeast Asia - Phubordee Bongkotvirawan; Natsuda Aumpan; Bubpha Pornthisarn; Soonthorn Chonprasertsuk; Sith Siramolpiwat; Patommatat Bhanthumkomol; Pongjarat Nunanun; Navapan Issariyakulkarn; Varocha Mahachai; Kammal Kumar Pawa; Ratha-korn Vilaichone (Women's Health Reports)
Introduction: Association of Southeast Asian Nations (ASEAN) countries have high Helicobacter pylori infections, and gastric cancer (GC) is a leading fatal cancer in this region, especially in female patients. This study aimed to compare clinical manifestations, histopathological subtypes, and prognostic factors associated with the overall survival rate of female GC patients in this important region. Methods: This retrospective cohort study was conducted between 2007 and 2022 at a tertiary care center in Thailand. All clinical information, endoscopic findings, and histological types were extensively reviewed. Furthermore, all qualified studies in ASEAN published in PubMed and Scopus between 2000 and 2022 were extracted and thoroughly analyzed. Young female GC patients are defined as those ≤50 years of age. Results: A total of 98 Thai female GC patients were included, with a mean age of 58.99 ± 14 years; 70.4% were elderly women. The common presenting symptoms were weight loss (69.4%) and dyspepsia (68.4%). Younger female GC patients had significantly more common diffuse-type GC than elderly female GC patients (82.8% vs. 53.6%, p-value = 0.007). Moreover, elderly female GC patients demonstrated significantly better survival than younger female GC patients (44.8% vs. 20.7%, odds ratio = 3.49; 95% confidence interval: 1.20–10.14, p-value = 0.022). Furthermore, a total of 1,491 female GC patients from ASEAN were reviewed and included in this study, aged 15 to 93 years. The top three countries with the highest proportion of female GC from ASEAN were Indonesia (66.7%), Thailand (44.9%), and Singapore (38.4%). Conclusion: GC in women is not uncommon in ASEAN and presents at an advanced stage with a grave prognosis. This study showed that ASEAN countries with the highest disease burden were Indonesia, Thailand, and Singapore. Overall, survival rates for female GC patients in ASEAN countries were relatively low, highlighting the need for proactive measures such as intensive H. pylori eradication and the development of early detection methods for GC.